2016
DOI: 10.1177/1076029616637440
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Renal Dysfunction Indicators in Normotensive Patients With Acute Pulmonary Embolism

Abstract: There is a close relationship between RD and APE prognosis. We conclude eGFR is a potential prognostic marker for risk stratification in normotensive patients with APE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
6
0
3
Order By: Relevance
“…Similarly, Altınsoy et al demonstrated that the elevated BUN levels, which is also a contributor to plasma osmolality, may have a predictive value for in-hospital and early mortality among patients admitted with APE. 15 Moreover, in a recent study that consisted of 252 consecutive APE patients, the researchers revealed that an admission BUN levels above 34.5 mg/dL is a predictor of in-hospital mortality among these patients. 9 Besides that, in an experimental study, the pulmonary effects of the hypernatremia were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Altınsoy et al demonstrated that the elevated BUN levels, which is also a contributor to plasma osmolality, may have a predictive value for in-hospital and early mortality among patients admitted with APE. 15 Moreover, in a recent study that consisted of 252 consecutive APE patients, the researchers revealed that an admission BUN levels above 34.5 mg/dL is a predictor of in-hospital mortality among these patients. 9 Besides that, in an experimental study, the pulmonary effects of the hypernatremia were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with APE classified to intermediate-risk class are the most heterogeneous group, although the previous attempt to divide this broad category into two subgroups, intermediate-high and intermediate-low risk [ 2 ], was unsuccessful to distinguish a group of higher mortality. Altinsoy et al [ 30 ] presented in the multivariate analysis that GFR estimated by CKD-EPI or MDRD together with positive troponin concentration are independent predictors of adverse outcome in normotensive patients with APE. Moreover, eGFR was correlated with RV dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…As with similar evaluation of registry data, there are inherent limitations to this type of study, mainly related to known or unknown confounding factors. Finally, our study used the MDRD formula in order to estimate eGFR although the CKD-EPI formula showed its superiority in analyzing the prognosis of normotensive patients with APE in a previous study [23].…”
Section: Discussionmentioning
confidence: 99%